Antusiasme Kerja Pegawai dalam Mengimplementasikan Sistem Informasi Berbasis Online di Perguruan Tinggi (Jurnal Strategi dan Bisnis, 2014)
Technology information and communication has become important in any aspect of modern live. Technology information and communication make communication of between human and between organizations becomes efficient and quick. The implications, today in the operation all organization in all activities have to use of develop of technology. The implication of application of technology is makes the big change in any aspect of organization operational, not exception in the university, especially in the implementation of information system-based online. The problem in how the level of enthusiasm of employees to implementation of modern information which always change, especially in university. Keywords: enthusiasm, information system, online